The Efficacy and Safety of Low‐ and High‐ Dose Fixed Combinations of Irbesartan/Hydrochlorothiazide in Patients With Uncontrolled Systolic Blood Pressure on Monotherapy: The INCLUSIVE Trial - Neutel, Joel M. (J Clin Hypertens (Greenwich), 2007)
This multicenter, prospective, open‐label, single‐arm study determined the efficacy and safety of irbesartan/hydrochlorothiazide (HCTZ) fixed combinations in patients (n=1005), aged 18 years and older, with uncontrolled systolic blood pressure (SBP) of 140–159 mm Hg (130–159 mm Hg for type 2 diabetes mellitus) after at least 4 weeks of antihypertensive monotherapy. Treatment was sequential: placebo (4–5 weeks), HCTZ 12.5 mg (2 weeks), irbesartan/HCTZ 150/12.5 mg (8 weeks), and irbesartan/HCTZ 300/25 mg (8 weeks). Enrolled patients (n=844) were aged 57.3±11.2 years; 52% were women, 23% were African American, and 14% were Hispanic. Thirty percent had type 2 diabetes mellitus, 46% had metabolic syndrome, and baseline blood pressure was 154.0±10.3/91.3±8.8 mm Hg. The mean change in SBP from placebo end to the primary end point, Week 18 (intent‐to‐treat population, n=736) was −21.5±14.3 mm Hg (p<0.001). The mean change in diastolic blood pressure (DBP) was −10.4 ±8.7 mm Hg (p<0.001). The mean Week 18 SBP/DBP was 132.9±13.8/81.1±9.7 mm Hg. Overall, 77% (95% confidence interval, 74%–80%) of patients achieved SBP goal (<140 mm Hg; <130 mm Hg for type 2 diabetes mellitus); 83% (95% confidence interval, 80%–86%) achieved DBP goal (<90 mm Hg; <80 mm Hg for type 2 diabetes mellitus); and 69% (95% confidence interval, 66%–72%) achieved dual SBP/DBP goal. Treatments were well tolerated. This irbesartan/HCTZ treatment regimen achieved SBP goals in more than 75% of patients uncontrolled on monotherapy.